People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. The leaders are walking by a building which is clearly showing their reflections. There are parked vehicles on the street and trees in the background. Some of the participants are wearing a tee shirt that reads: "Walk for women. YWCA 1986" and some are carrying balloons.